Näen lintujen lentävän etelään ‘I see birds flying south’ – About an interesting case of syntactic ambiguity in Finnish - Bielecki, Robert (Lingua Posnaniensis, 2018)
An attempt is made to describe the syntactic structure of the Finnish non-attributive participial construction of the type Näen lintujen lentävän etelään ‘I see birds flying south’ by investigating the actual construction, and not a cognate sentence from which the construction is said to be derived. The analysis leads to the conclusion that two parts can be distinguished in the construction. The words belonging to the first part clearly determine syntactically the participle, e.g. lentävän ← etelään. In the case of the words of the other group, however, there exists no syntactic test by which it would be possible to verify the direction of the relation of syntactic determination. This part of the construction is therefore to be conceived of as syntactically ambiguous, i.e. both lintujen ← lentävän and lintujen → lentävän. It represents the neutralization of two structures: (i) a nominal structure (lintujen lentäminen ‘birds’ flying’) and (ii) a nominal-verbal structure (linnut lentävät ‘birds are flying’). In consequence of this fact, different syntactic interpretations of the construction do not give rise to different semantic interpretations.